KONTRIBUSI BIMWINCATIN DI KUA KECAMATAN CURUG DALAM MENINGKATKAN PEMAHAMAN TENTANG PEMBAGIAN PERAN RUMAH TANGGA - Sinta Nuraini; Silvia Indriani; Hunainah (STKIP Subang, 2026)
This study aims to analyze the contribution of the Pre-Marital Guidance Program (Bimbingan Perkawinan Calon Pengantin/Bimwincatin) at the Office of Religious Affairs (KUA) of Curug District in improving prospective couples’ understanding of household role distribution. The distribution of household roles is an essential aspect of family life as it relates to the implementation of husbands’ and wives’ rights and obligations, family decision-making, financial management, and child-rearing responsibilities. This research employed a descriptive quantitative approach using a survey method. Data were collected through questionnaires distributed to prospective brides and grooms who had participated in the Bimwincatin program at KUA Curug District. The research instrument was developed based on indicators of understanding household role distribution, including knowledge of marital rights and obligations, cooperation in household activities, joint decision-making, and family responsibilities. In addition, this study was supported by literature reviews and documentation related to the implementation of the Bimwincatin program. The findings are expected to provide an overview of participants’ level of understanding after attending the program and to describe the contribution of Bimwincatin in preparing prospective married couples to build harmonious families. The results of this study are expected to serve as an evaluation and development reference for improving the effectiveness of premarital guidance programs in society.